An updated and illustrated dichotomous key for the chagas disease vectors of Triatoma brasiliensis species complex and their epidemiologic importance - Dale, Carolina; Almeida, Carlos Eduardo; Mendonça, Vagner José; Oliveira, Jader [UNESP]; da Rosa, João Aristeu [UNESP]; Galvão, Cleber; Costa, Jane (Pensoft Publishers, 2018)
In the subfamily Triatominae, Triatoma exhibits the largest number of species, which are arranged in complexes. For the T. brasiliensis species complex, recent investigations based on results of geometric morphometrics combined with phylogeny have provided evidence that it should be composed of seven species: T. brasiliensis, T. bahiensis, T. juazeirensis, T. lenti, T. melanica, T. petrocchiae, and T. sherlocki, in which T. brasiliensis is divided in two subspecies: T. b. brasiliensis and T. b. macromelasoma. A taxonomic key is presented to identify each taxon. Among members of this complex, T. b. brasiliensis is the most important in an epidemiologic context, due to its high prevalence in natural infection by Trypanosomacruzi combined with a pronounced adaptation to domiciliary habitats. However, some members may be currently invading and colonizing homes, a process known as domiciliation. Therefore, the key presented here may be potentially useful for researchers as well as those involved in vector control measures.
Keywords: Kissing bugs; Morphological key; Species group